Perceptions of Risk: Perspectives on Crime and Safety in Public Housing for Older Adults. (26th October 2021) - Sheppard, Christine L; Gould, Sarah; Austen, Andrea; Hitzig, Sander L
Abstract: Background and Objectives: An increasing number of older adults are aging in place in public housing. Public housing is perceived to have higher rates of crime that have detrimental impacts on health and well-being. We used a qualitative approach to understand the experiences of safety and unsafety for older adults in public housing. Research Design and Methods: Participants included older adult tenants ( n = 58) as well as service providers ( n = 58) who offer supports directly in the buildings. Semistructured qualitative interviews and focus groups were used to explore (a) what makes the buildings feel unsafe, (b) how safety concerns affect access to support services, and (c) strategies used to promote safety. Results: Participants acknowledged the importance of safety for creating a home-like environment; however, many described feeling unsafe at home or work. Participants described extreme examples of antisocial behaviors that were pervasive and viewed as commonplace. Lack of building security was a key issue, which was compounded by a perceived lack of accountability. While service providers were willing to accept a certain level of risk, many acknowledged that unsafe situations forced them to withdraw in-home services or stop community programs, further contributing to feelings of unsafety. In the absence of effective formal security, participants described several measures taken to mitigate risk. Discussion and Implications: Our findings point to the need for enhanced physical and environmental safety infrastructure, improved building management, increased on-site security, as well as other proactive measures to reduce risk by creating a greater sense of connection and community within the buildings.